THE INFLUENCE OF MOTIVATION, ATTITUDES, AND MODERATION OF KNOWLEDGE FOR COMPLIANCE ENHANCEMENT - Viky Santy Theresia; Agusdini Banun Saptaningsih; Hasyim Hasyim (Magister Manajement Studies Program, 2022)
Abstract – Compliance in filling out medical records critical as it has significant impact on frequently arising problems, such as incomplete filling and less specific doctors' writing on the diagnosis. This situation will impact hospital internally and externally since data processing results are the basis for hospital reports. This study aims to analyze how motivation and attitudes influence compliance levels of doctors in filling out medical resumes, which are moderated by knowledge at Ananda Hospital, Bekasi. This research was a causality research design with one short study time dimension using comparative quantitative analytical survey. A purposive sampling technique was used, and determined that the sample size was fifty people. Based on the analysis result, there were values of R2 and R3 in the linear regression analysis, motivation for compliance was 12.9%, and attitudes for compliance was 13.5%. In comparison, after testing the equation with multiple regression, the value of R1 rose to 18.2%. Therefore, good knowledge will strengthen the relationship between motivation and attitudes toward doctor's compliance in filling out a medical resume.